1975
DOI: 10.1002/1097-4679(197504)31:2<356::aid-jclp2270310244>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual differerentiation and defense mechanisms in alcoholics

Abstract: PROBLEM Alcoholics, as a clinical population, have been found in previous research to be markedly field-dependent when compared with nonalcoholic normal and hospitalized psychiatric control groups (12, I s ) . Further evidence tends to substantiate the presence of cognitive and personality correlates of limited perceptual diff erentiation in alcoholics. Karp, Poster, and Goodman'll) found alcoholic women to have a less sophisticated body concept, as assessed by figure-drawing tests, than nonalcoholic controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This was found to be true within the narrower range of early adulthood (GIeser & Ihilevich, 1969) as well as over the broader range, through later adulthood (Donovan, Hague, & O'Leary, 1975;Rohsenow et aI., 1978;Wilson, 1982). Only one study reports on the relationship between defense choice and education, unconfounded by age (Rohsenow et aI., 1978): PRN correlated positively with years of education, REV and T AS correlated negatively, and both TAO and PRO were unrelated.…”
Section: Age Education Birth Order and Ethnic Groupmentioning
confidence: 99%
“…This was found to be true within the narrower range of early adulthood (GIeser & Ihilevich, 1969) as well as over the broader range, through later adulthood (Donovan, Hague, & O'Leary, 1975;Rohsenow et aI., 1978;Wilson, 1982). Only one study reports on the relationship between defense choice and education, unconfounded by age (Rohsenow et aI., 1978): PRN correlated positively with years of education, REV and T AS correlated negatively, and both TAO and PRO were unrelated.…”
Section: Age Education Birth Order and Ethnic Groupmentioning
confidence: 99%
“…Ln one approach, clinical assessments of defenses were made. The clinical techniques used have included (he Rorschach (e.g., Hertini, 1962;Levine & Spivak, 1964;Morrison & ('enters, 1069;Schimek, 1968); an interview (Witkin et al, 1954(Witkin et al, , 1972 or therapy interactions (Safer, 1975); a battery of psychological tests and behavioral observations (Gardner & Moriarty, 1968); Blacky Pictures and the Sentence Completion Test (Lutzky & Schmeidler, 1963;Silverstone, 1966); and the Defense Mechanism Inventory, developed by Gleser and Ihilevich (1969) (e.g., Bogo, Winget, & Gleser, 1970;Donovan, Hague, & O'Leary, 1975;Erickson, Smyth, Donovan, & O'Leary, 1976;Williamson, 1977). In another kind of study, repressers and isolators were identified through performance on a metacontrast situation (Almgren, 1971 ;Nilsson & Almgren, 1970).…”
Section: Specialized Defensesmentioning
confidence: 99%
“…The subject is asked to choose the alternative that best represents how he would react to that situation. Studies with the Defense Mechanism Inventory have consistently shown that field-independent people are prone to use "turning against ob-ject" as a characteristic defense, and fielddependent subjects "turning against self" (Bogo, Winget, & Gleser, 1970;Donovan, Hague, & O'Leary, 1975;Gleser & Ihilevich, 1969;Ihilevich, 1968;Ihilevich & Gleser, 1971).…”
Section: Handling Of Hostilitymentioning
confidence: 99%